Polarization-Independent Focusing Vortex Beam Generation Based on Ultra-Thin Spiral Diffractive Lens on Fiber End-Facet - Luping Wu; Zhiyong Bai; Rui Liu; Yuji Wang; Jian Yu; Jianjun Ran; Zikai Chen; Zilun Luo; Changrui Liao; Ying Wang; Jun He; George Y. Chen; et al. (Photonics)
An ultra-thin spiral diffractive lens (SDL) was fabricated by using focused ion beam milling on a fiber end-facet coated with a 100 nm thick Au film. Focusing vortex beams (FVBs) were successfully excited by the SDLs due to the coherent superposition of diffracted waves and their azimuth dependence of the phase accumulated from the spiral aperture to the beam axis. The polarization and phase characteristics of the FVBs were experimentally investigated. Results show that the input beams with various polarization states were converted to FVBs, whose polarization states were the same as those of the input beams. Furthermore, the focal length of the SDL and the in-tensity and phase distribution at the focus spot of the FVBs were numerically simulated by the FDTD method in the ultra-wide near-infrared waveband from 1300 nm to 1800 nm. The focal length was tuned from 21.8 μm to 14.7 μm, the intensity profiles exhibited a doughnut-like shape, and the vortex phase was converted throughout the broadband range. The devices are expected to be candidates for widespread applications including optical communications, optical imaging, and optical tweezers.